Methadone Maintenance Therapy (MMT) in Malaysia: An observational clinical study - Almeman, Ahmad AbdulRahman; Ismail, Rusli; Mohamad, Nasir (Australasian Medical Journal, 2017)
Background Methadone is widely used to treat opiate addiction, in particular heroin. Proper administration via drug optimisation is the only way to achieve net clinical outcomes. Aims This is an observational cross-sectional study, sought to observe the clinical response to a methadone maintenance therapy (MMT) program. Methods Setting: Four treatment clinics in Kuala Lumpur, Malaysia. Patients and methods: One-hundred and twenty-two methadone patients. Their demographic characteristics, medical history, methadone doses, duration in the program, and compliance rates were recorded. Main outcome measures: The opiate withdrawal scale was used to assess the severity of withdrawal symptoms. Results The mean methadone dose was 50mg (range, 20–160mg). The minimum recorded duration in the MMT program was three months, the maximum was 40 months, and the mean was seven months. 90 per cent of the patients were addicted to multiple substances; of those, 70 per cent were addicted to three or more substances. Many patients reported cravings and seeking behaviours while on methadone. Conclusion Gradual increments in methadone doses are relatively safe, but patients should be monitored daily. Doses should be increased to control withdrawal symptoms. Despite optimal dosing, cravings and drug-seeking behaviours may not be controlled in some patients, and an alternative to methadone may be an option.